Combination Effects of African Leaf Ethanol Extract (Vernonia amygdalina Del.) with Red Onion Peel (Allium cepa L.) as Antidiabetes in Streptozotocin-induced Mice - Setiani, Lusi Agus; Wiendarlina, Ike Yulia; Marcella, Nurma (Tropical Biopharmaca Research Center, IPB University, 2024)
Type 2 diabetes arises when the body becomes resistant to insulin or when the pancreas fails to produce sufficient insulin. This study aimed to evaluate the antidiabetic effects of reducing blood glucose levels in white male mice through the administration of an ethanol extract of African leaves and onion peel, as well as to determine the duration of these effects. Streptozotocin was used to induce diabetes in the mice, and the experiment was conducted over a period of 21 days. The mice were divided into seven groups: Group 1 received a placebo (CMC Na 0.5%), Group 2 received glibenclamide (0.013 mg/20 g body weight), Group 3 received a single dose of African leaf extract (4.2 mg/20 g BW), Group 4 received a single dose of onion peel extract (4 mg/20 g BW), and Groups 5, 6, and 7 received combinations of African leaf and onion peel extracts at ratios of 1:1, 1:2, and 2:1, respectively. The results demonstrated that the combined administration of African leaf and onion peel extracts significantly reduced blood glucose levels, with decreases of 44.701%, 49.929%, and 51.996% in the 1:1, 1:2, and 2:1 group, respectively. The 1:1 combination was particularly effective, showing a reduction in blood glucose levels comparable to the positive control, which achieved a 45.957% decrease. The administration of the test preparations effectively reduced blood glucose levels over 21 days, with significant reductions observed on both the 14th and 21st days.